Estimation of foliar optical properties from vegetation using equivalent radiative media and n-parametric spaces - Paz-Pellat, Fernando (REVISTA TERRA LATINOAMERICANA, 2013)
Estimation of biochemical properties of the vegetation canopy is intrinsically coupled to the structural properties (leaf area index and vegetation coverage), so that their joint estimation poses a mathematically indeterminate problem to solve. In response, this paper discusses a solution scheme to convert radiatively heterogeneous medium (need to estimate the structural and biochemical parts) to a homogeneous (single estimate of the biochemical part). In order to operate the concept of media conversion, it is necessary to use the paradigm of equivalent media, which requires effective parameters. Estimating the infinite reflectances (homogeneous media) using nparametric spaces is discussed considering the estimation problems (error propagation) associated therewith. The generalization to supra-parametric spaces is introduced as a way of compacting the spectral dynamics associated with vegetation growth for a specific operating environment.